Social Capital and Subjective Well-Being (SWB) of Public Rental Apartment Occupants: Study at Jambangan Rusun Surabaya (Jurnal Bina Praja, 2017)
Housing needs in major cities in Indonesia are increasing due to urbanization. The solution taken by the government is to provide rental housing (rusunawa). Low income families who initially live in slums need some adaption when moving into the rusunawa. The purpose of this research is to analyze the socio-demographic relationships of families, social capital and subjective well-being (SWB). Using quantitative method and household survey, this study was conducted by giving questionnaires and interview to 90 residents of 396 rusunawa units. The study use regression analysis. Thus, the result shows that social capital, the social network, and trust, determine the SWB. If SWB is an indicator of the process of adaption of a person or family in a new place, in this study, we concluded that these two variables were very important for the resident. Using social networking and trust, these residents can adjust to a new housing milieu.
Keywords: Rental Flats (Rusunawa); Urban Poor People; Social Capital; Trust; SWB